Impact of silver nanoparticles on the ultraviolet radiation direct and bystander effects on TK6 cell line - Zohreh Eftekhari-Kenzerki (Journal of Medical Physics, 2019)
Purpose/Aim: Ultraviolet C (UVC) radiation is harmful to cells and living organisms that cause direct and indirect DNA damage. UVC can also increase the inflammatory genes expression such as COX-2 that results in elevated oxidative stress that plays a role in radiation-induced bystander effect (BSE). Silver nanoparticles (AgNPs) have used widely in commercial and medical products and the toxicological risks of AgNPs must be determined. The aim of this study was to investigate the direct and BSEs of UVC radiation and AgNPs on TK6 cell line. Materials and Methods: TK6 cells were exposed to AgNPs (10 μg/ml, 1 h). Then, they were exposed to UVC and to determine the BSEs of radiation, the irradiated cells media were transferred to nonirradiated cells. Expression level of H2AX and COX-2 mRNAs were examined by quantitative real-time PCR and 8-OHdG formation was examined by ELISA. The cell viability examined by MTT assay. Results: P < 0.05 was considered as the level of significance. The results showed that the mean expression level of H2AX mRNA in the AgNPs + UVC group increased significantly in comparison with UVC group. 8-OHdG increased significantly in the BSE of UV group in comparison with sham control of BSE. COX-2 mRNA increased significantly in the BSE of AgNPs + UVC with sham control in BSE. Conclusions: Our findings showed the induced DNA damage in TK6 cell by AgNPs and UVC radiation and also were seen BSE.